Improving Presentation Skills in Japanese through Project Based Learning in Kaiwa VI Lesson - Mufidah, Imroatul (Universitas Negeri Jakarta, 2022)
This research aims to determine the presentation ability of Japanese Language Education students at the State University of Jakarta in Kaiwa VI lesson using conventional learning methods and Project Based Learning models, to determine the improvement in presentation skills of students who receive Project Based Learning, as well as to determine student responses on the application of the Project Based Learning model in Kaiwa VI lesson. This is motivated by the problems found in the Kaiwa VI lesson, including: the lack of student's ability to think critically in solving a problem, and students are less able to understand the content of research so that they are not optimal in presenting the research results. This is influenced by the lack of a literacy process and the lack of an independent data collection process by students because so far students have only presented the results of other people's research. Project Based Learning is a student-centered learning model to conduct a deep investigation of a topic. The method used is True Experimental Design in the form of Posttest Only Control Group Design research. The sample in this research were students who took Kaiwa VI lesson which were divided into experimental groups and control groups. The results showed that students who received the Project Based Learning model got an increase in presentation skills better than students who received conventional learning. This is shown in the results of the posttest data analysis, the experimental group has an average of 5.6 points higher than the control group. Student responses regarding the implementation of the Project Based Learning model are quite good.